MEMAHAMI ISLAM LOKAL MELALUI KITAB SERIBU MASAâ€™IL: STUDI KOMPARASI TEKS ARAB-MELAYU - Alindah, Lutfiyah (Paramasastra: Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2015)
TheÂ  spreadÂ  andÂ  developmentÂ  ofÂ  IslamÂ  inÂ  theÂ  IndonesiaÂ  notÂ  onlyÂ  brought Islam together, but also brought Islamic culture in the form of literature. The developmentÂ  in teaching IslamicculturalÂ  traditionÂ  isÂ  importantÂ  inÂ  the process of Islamization.Â  ManyÂ  booksÂ  wereÂ  translated,Â  composedÂ  orÂ  adaptedÂ  toÂ  many languages in the archipelago. The books are compiled in what is known as sastra kitabÂ  (literatureÂ  ofÂ  IslamicÂ  theology).Â  ItsÂ  twoÂ  versions,Â  theÂ  MasailÂ  Sayyidi 'Abdullah bin SalamÂ  lin NabiÂ  inÂ  the Arabic version orÂ  Seribu Masaâ€™ilÂ  in Malay version,Â  areÂ  stillÂ  preserved.Â  BothÂ  ofÂ  theseÂ  textsÂ  areÂ  partÂ  ofÂ  theÂ  processÂ  of translationÂ  fromÂ  ArabicÂ  textsÂ  intoÂ  MalayÂ  textÂ  whichÂ  haveÂ  variationsÂ  eitherÂ  in structureÂ  linguisticÂ  or meaning.ThisÂ  paperÂ  examinesÂ  theÂ  variationsÂ  occurringÂ  in process of translation between Arabic text and Malay text, and how the variations are manifestedÂ  inÂ  theseÂ  twoÂ  texts. ThisÂ  researchÂ  isÂ  important becauseÂ  itÂ  looks at Sirah nabawiyah (history ofÂ  the prophet)Â  that documents both written and verbal teachingsÂ  ofÂ  Islam.Â  InÂ  addition,Â  thisÂ  studyÂ  containsÂ  theÂ  theologicalÂ  valuesÂ  and dialogue between Muslims and non-Muslims. By using George Steinerâ€™sÂ  theory, this study tries to examine the difficulties and the paradoxes created by translation fromÂ  oneÂ  languageÂ  toÂ  another.ThisÂ  studyÂ  demonstratesÂ  thatÂ  theÂ  finalÂ  translation between MasÄâ€™ilÂ  SayyidiÂ  â€˜AbdullÄhÂ  BinÂ  SalÄmÂ  li-NabÄ«Â  textÂ  andÂ  Seribu Masa'il have variations both in the structure of linguistics and meanings.Â